Experimental and Numerical Investigation of the Effects of Different Draft and Wave Frequency Combinations on the Performance of a Fixed OWC Wave Energy Converter - Öztürk, Deniz; Şerifoğlu, Mehmet Ozan (Galenos Yayinevi, 2021)
The oscillating water column (OWC) device is a versatile type of wave energy converter, which is one of the promising and popular systems in the use of sustainable supplies of energy. The present research aims to investigate the hydrodynamic performance of a cylindrical OWC device within several approaches, thereby observing the effects of varying wave heights and vertical positions on the flow inside the device. A series of experiments and numerical analyses were performed on a fixed OWC device with an open orifice for three different drafts (0.25, 0.40, and 0.55 m) and regular waves with frequencies ranging between 0.4 Hz and 1.2 Hz. Present results were compared with the results derived from the analytical calculations. The trends observed in the analytical solutions in a response amplitude operator for the heave motion of the internal water free surface with the wave frequency variation for all drafts were consistent with the numerical and experimental results. The findings reveal that the maximum water displacement inside the OWC increases as the draft increases, and the optimal frequency at which this value appears decreases.
Keywords: regular waves; Naval architecture. Shipbuilding. Marine engineering; oscillating water column; VM1-989; computational fluid dynamics; volume of fluid; renewable energy